Structural Barriers to Intergovernmental Relationships in Nepal - Acharya, Keshav K.; Kandel, Resham; Upadhyay, Parshuram (Dhaulagiri Journal of Sociology and Anthropology, 2024)
This paper examines the role of Intergovernmental Relations (IGR) in shaping interactions among Nepal's different levels of government. This article examines how IGR has evolved, its functionality, and its challenges, focusing on the structural and systemic barriers to its effectiveness. Using qualitative research, data was collected through interviews with 28 key informants, including members of the National Coordination Council, chief ministers, LG Associations, and federal ministries from April to October 2022. Findings show that, despite constitutional and legal mechanisms like the Constitutional Bench, Interprovincial Council, and National Coordination Council, IGR remains inefficient. Key barriers include a lack of willpower, self-interest, and a failure to innovate. These issues hinder the constitutional bench, with over 300 pending cases, and the IPC struggles due to the Prime Minister’s reluctance to devolve power. The NCC faces internal political conflicts, and the Intergovernmental Fiscal Council deals with grant distribution, tax collection, and fiscal federalism challenges. Other challenges include weak participatory practices, complex procurement, and a rigid resource distribution system. As a result, the paper demonstrates that federalism implementation still faces significant challenges despite federal, provincial, and local cooperation. The issues include ambiguous jurisdictions, political disagreements, inefficient bureaucracies, and unclear fiscal mechanisms. It is essential for Nepal's federalism to be effectively implemented that there is strong political commitment, supportive institutions, and a culture of governance emphasizing policy coherence and public service delivery.